Modeling Water Stress Effect on Soil Salinity - Tayfur, Gökmen; Tayfur, Gökmen (Springer Verlag, 2011)
As it is widely known the earth is experiencing a climate change. The primary effect of this change is the increase trend in global temperature. This, in turn, results in increased number of events in flooding, and drought in different parts of the world. A secondary effect is the change in water and soil salinity. A considerable portion of the cultivated land in the world is affected by salinity, limiting productivity potential. About 20 million ha of total 230 million ha of irrigated land in the world are salt affected. The climate change is expected to worsen this situation. This study explores the water stress effect on soil salinity. For this purpose, a model is developed to simulate salt transport in a layered soil column. The soil salinity transport model development involves two parts: (1) modeling salt movement through sail layers due to runoff, percolation, and lateral subsurface flow, and (2) modeling dissolution and precipitation of gypsum which acts as sink or source for salts in soil. The model is calibrated and validated with measured data. The soil is irrigated under optimal and water stress irrigation conditions. The major model parameters affecting the soil salinity are found to be wilting point, field capacity, hydraulic conductivity, initial soil salinity, and soil gypsum concentration. The results have revealed that water stress results in high concentration of salt accumulation in soil columns.
Keywords: Salinity; Water stress; Soil